Nonstandard Work and Child Care Choices of Married Mothers - Jean Kimmel; Lisa Powell (W.E. Upjohn Institute for Employment Research, 2001)
The focus of this paper is to examine the interplay between nonstandard employment and child care choice decisions of married mothers with young children. We draw on the 1992/93 Survey of Income and Program Participation to estimate two related econometric models of child care choice that include the choice among center, sitter, relative and parental care. First, controlling for the potential endogeneity of the nonstandard work decision, we find that being a nonstandard worker significantly reduces the likelihood of using formal modes of child care such as center and sitter care. In our second model, where we jointly estimate the work status and child care choice decisions of mothers, we find that the standard versus nonstandard work decision is more responsive to the price of child care. Finally, we conclude the paper by discussing potential policy solutions to improve the child care options for mothers with young children working in nonstandard jobs.
Keywords: J2; J13; 330; child care; part-time; temporary; mothers; Kimmel; Powell